Professional development for an Australian Library and Information Studies (LIS) educator - Smith, Kerry (IFLA, 2006)
The library profession in Australia, as over the world, is very feminised such that over 80% of those employed are women. Add to this the youngness of the country and the reasonably recent advent of university-level education for the LIS library professional and we find that it is rare for an Australian professional librarian who decides to become a library educator at a university to enter the academic world of LIS teaching with a PhD. An anecdotal view from some local professionals is that they "know it all" and even if they were to become an academic, they might gain a masters qualification (if they do not already have one) though it is less likely that they would wish to undertake and finish a PhD. Yet most of the universities in Australia demand a PhD qualification from anyone who is serious about continuing in an academic role. It could be argued that in the Australian LIS academic context, gaining a PhD is professional development enough, particularly since undertaking such a research project whilst working full or even part time takes dedication and time. Can the LIS academic then afford to rest? The paper discusses a number of professional development possibilities for the Australian LIS academic. Those drawn from the author's personal experience include academic management, further study, pursuing research and election to local government. How useful are such professional development ventures and for whom are they of use? What real contribution will they make to the future of the Australian LIS academic and is the future of the profession considered in such professional development pathways? The paper will evaluate professional development ventures in light of many factors including gender, age, university and professional politics, academic and professional obligation, and preference. The paper concludes with comments on the professional future for LIS academics in Australia in light of possible professional development decisions.